The strenghth of glulam beam made-up of weaker species as inner layers and harder species as outer layers - 254363 Khusairi Namrum (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2006